The biomechanical, biochemical, and morphological properties of 19 human cadaveric lower limb tendons and ligaments: an open-access data set - Ashton, Dylan M.; Blaker, Carina L.; Hartnell, Nicholas; Haubruck, Patrick; Liu, Ying; Hefferan, Samantha A.; Little, Christopher B.; Clarke, Elizabeth Climenko (The American journal of sports medicine, 2024)
BACKGROUND: Methodological heterogeneity hinders data comparisons across isolated studies of tendon and ligament properties, limiting clinical understanding and affecting the development and evaluation of replacement materials. - PURPOSE: To create an open-access data set on the morphological, biomechanical, and biochemical properties of clinically important tendons and ligaments of the lower limb, using consistent methodologies, to enable direct tendon/ligament comparisons. - STUDY DESIGN: Descriptive laboratory study. - METHODS: Nineteen distinct lower limb tendons and ligaments were retrieved from 8 fresh-frozen human cadavers (5 male, 3 female; aged 49-65 years) including Achilles, tibialis posterior, tibialis anterior, fibularis (peroneus) longus, fibularis (peroneus) brevis, flexor hallucis longus, extensor hallucis longus, plantaris, flexor digitorum longus, quadriceps, patellar, semitendinosus, and gracilis tendons; anterior cruciate, posterior cruciate, medial collateral, and lateral collateral ligaments; and 10 mm-wide grafts from the contralateral quadriceps and patellar tendons. Outcomes included morphology (tissue length, ultrasound-quantified cross-sectional area [CSAUS], and major and minor axes), biomechanics (failure load, ultimate tensile strength [UTS], failure strain, and elastic modulus), and biochemistry (sulfated glycosaminoglycan [sGAG] and hydroxyproline contents). Tissue differences were analyzed using mixed-model regression. - RESULTS: There was a range of similarities and differences between tendons and ligaments across outcomes. A key finding relating to potential graft tissue suitability was the comparable failure loads, UTS, CSAUS, sGAG, and hydroxyproline present between hamstring tendons (a standard graft source) and 5 tendons not typically used for grafting: fibularis (peroneus) longus and brevis, flexor and extensor hallucis longus, and flexor digitorum longus tendons. - CONCLUSION: This study of lower limb tendons and ligaments has enabled direct comparison of morphological, biomechanical, and biochemical human tissue properties-key factors in the selection of suitable graft tissues. This analysis has identified 6 potential new donor tissues with properties comparable to currently used grafts. - CLINICAL RELEVANCE: This extensive data set reduces the need to utilize data from incompatible sources, which may aid surgical decisions (eg, evidence to expand the range of tendons considered suitable for use as grafts) and may provide congruent design inputs for new biomaterials and computational models. The complete data set has been provided to facilitate further investigations, with the capacity to expand the resource to include additional outcomes and tissues.
Gesehen am 28.01.2025